Incidental Finding of a Supernumerary Tooth Fused to a Mandibular Second Molar Using Cone Beam Computed Tomography (CBCT): A Case Report - Negin Soghli; Mehrdad Panjnoush; Maryam Johari (International Journal of Scientific Research in Dental and Medical Sciences (IJSRDMS), 2020)
Twinned tooth is a rare phenomenon among dental anomalies, which may develop during the tooth bud morphodifferentiation stage. Twinned tooth refers to the fusion of two adjacent tooth buds or gemination of the single bud. Clinically it is difficult to differentiate between fusion and gemination. During this anomaly, primary dentition is mostly affected rather than permanent dentition and predominantly it is observed unilaterally. Gemination is more common in the anterior region of maxilla, while fusion mainly takes place in the anterior mandibular region. No definite etiology for these anomalies is reported but genetic and environmental factors are mostly mentioned as potential risk factors. This paper describes a case of fusion of the second mandibular molar with a supernumerary tooth. Twinned teeth can cause clinical problems such as dental caries, periodontal and aesthetic problems. So early diagnosis can be achieved through careful clinical and radiographic examinations; however, in most cases of twinned teeth, no major clinical problem is reported.